Constricting Gaps: Protocol development, implementation challenges and lessons learned for the reality map of unmet needs for Palliative Care Interventions in advanced cancer patients study in Romania and Switzerland - Natalie Kalbermatten; Razvan Curca; Alexandru Grigorescu; Daniela Mosoiu; Florina Pop; Vladimir Poroch; Ariana Rosiu; Patriciu Achimas-Cadariu; Florian Strasser (Contemporary Clinical Trials Communications)
Background: Patients with advanced cancer experience many symptoms and needs requiring a Palliative Care Intervention (PCI). Identifying gaps between needs for PCIs and experienced delivery may improve health care, furthermore the association of gaps with quality indicators (QI). The multicentre Romanian (RO)-Swiss (CH) reality map study implemented a novel protocol based on needs concepts and culturally adapted quality indicators (QI). Methods: An interactive mapping guide measuring unmet needs for PCIs monthly over six months, patient characteristics (cognition, EAPC basic data set, Cofactors) and QI (Inappropriate Anticancer Treatment, High Symptom Burden [IPOS, EQ5D], Repeated ER Admissions, Aggressive End-of-Life Care, and Quality of Death-and-Dying) were developed, applying swiss standards for quality assurance. A composite endpoint (QI, cofactors) was planned. Finally, local solutions responding to gaps were piloted. Results: From 308 patients (RO: 262, CH: 46, age 62j [mean], 74 % ECOG PS 1&2, 81 % current anticancer treatment) baseline and first follow-up data revealed main gaps (symptom management, spiritual needs, family support), country differences (e.g. illness understanding, spiritual needs) and a significant association of the number of gaps with depression. Later data become less, and data quality on QI variable, revealing gaps in research conduct competences, resources, and applicability of over-sophisticated quality assurance tools. Nevertheless, the unmet needs data promoted local initiatives, 81 patients participated in feasibility studies. Finally, the joint experience stimulated academic developments and national integration of palliative care into oncology. Conclusions: Pairing motivation and enthusiasm with more modest aims, feasibility testing of all outcomes and investment in research competences may disperse gaps.